Factors Responsible for Premature Discontinuation of Long Acting Reversible Contraceptives A Study Conducted In Model Family Planning Clinic of Dhaka Medical College Hospital Over A Period of One Year (Journal of Dhaka Medical College, 2020)
Background: Despite the improvement in availability and utilization of Long Acting Reversible Contraceptive (LARC) methods which comprises intrauterine contraceptive devices(IUCD) and implants, premature discontinuation is becoming a public health concern and its consequence may lead to failure of a program. Therefore identifying the causal factors are important for designing a strategy to overcome the problem.Objectives: To measure discontinuation of intrauterine contraceptive device (IUCD) and implants and identify baseline characteristics associated with premature discontinuation.Materials and Methods: This retrospective study was conducted among the clients attended in Model Family Planning Clinic of Dhaka Medical College Hospital from January,2018 to December, 2018. Records of all clients who discontinued LARC prematurely (before device expiration) and clients who wished for discontinuation but did not do so during this period were explored.Results:Total 233 implants were removed during the study period among them 87 were removed before their expiry date. Total 252 clients came for early removal (within 1 year of insertion) of cuT but only 39 were removed. On the other hand 82 clients came for premature discontinuation(after 1 year of their insertion) during this period, among which 18 were removed before the date of expiry. Side effects associated with the method itself and the procedure, expulsion, failure and other similar inconveniences contributed for discontinuation.Conclusions: Higher level of discontinuation of LARC may substantially contribute to high fertility rate, unwanted pregnancies and induced abortions. Also, premature termination makes the method less cost effective. Therefore appropriate counseling, follow up care and management of side effects along with information on contraceptive effectiveness, insertion and removal procedure are very important.J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 112-118